The Thought of Governing Country and Employing People in the Period of Emperor Wu of Han: -- Take the Appointment of Imperial History Officials as Examples - Wang, Ruorui (Transactions on Social Science, Education and Humanities Research, 2024)
The Han Dynasty is of great significance to the process of the unification of China, and the system of the Han Dynasty also laid the foundation for the political system of China for more than 1,000 years. Among them, Emperor Wu was the key figure in the transition of the Han Dynasty system. Scholars generally summarize the ruling thought of Emperor Wu of Han Dynasty as external Confucianism and internal law, which is not accurate. From the analysis of the selection and appointment of the imperial officials in the Emperor Wu's dynasty, we can find that Emperor Wu's governance and employment strategy are based on his own will, which reflects strong functionalism and totalitarianism. Confucianism, as the mainstream thought advertised at that time, was more of a decoration.